Hollow Cu@Y molecular sieve adsorbent and preparation method and application thereof

CN117019094BActive Publication Date: 2026-10-30TAIYUAN UNIVERSITY OF TECHNOLOGY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311265230.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-28
Publication Date
2026-10-30
Estimated Expiration
2043-09-28

AI Technical Summary

Technical Problem

该分子筛的静态平衡吸附硫容可达24.07mg/g,但吸附剂采用的锂渣前期处理步骤比较复杂,且锂渣含有大量金属元素,影响Y分子筛的结晶,静态吸附硫容相对较低

Benefits of technology

[0036]本发明采用配体保护-原位合成策略制备中空Cu@Y分子筛吸附剂,将原子分布的孤立Cu离子封装在空心FAU沸石中,其中的Cu物种与超笼和钠石笼共享的六元环中的框架氧形成了强烈的相互作用,而原位合成方法相较离子交换法和浸渍法,制备过程更加简便,省去了后处理步骤,节约了能耗。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117019094B_ABST
    Figure CN117019094B_ABST
Patent Text Reader

Abstract

The present application relates to a kind of hollow Cu@Y molecular sieve adsorbent and its preparation method, it is in copper amine complex aqueous solution Join aluminum source, alkali source and silicon source form original sol, add seed crystal to form original gel, in situ one-step hydrothermal crystallization reaction is removed in excess copper oxide in ammonium nitrate solution Reflux reaction, calcination obtains hollow Cu@Y molecular sieve adsorbent.The unique hollow structure of the molecular sieve adsorbent of the present application has significant adsorption enrichment effect, static adsorption sulfur capacity is large, desulfurization rate is high, suitable for the ultra-deep adsorption removal of thiophene sulfur in coking benzene.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of coking benzene desulfurization technology, and relates to molecular sieve adsorbents for ultra-deep removal of thiophene sulfides from coking benzene, particularly to a hollow Cu@Y molecular sieve adsorbent with high sulfur adsorption capacity and its preparation method. Background Technology

[0002] Benzene is an important industrial chemical raw material with a wide range of applications, including the production of synthetic resins, artificial fibers, pesticides, and dyes. Furthermore, a series of compounds generated from benzene through substitution, addition, and oxidation reactions can also be used as raw materials for the production of plastics, rubber, and fibers.

[0003] Benzene is mainly derived from petroleum benzene and coking benzene. Petroleum benzene resources are scarce, while coking benzene resources are relatively abundant. Given the shortage of petroleum resources and increasing demand for benzene, coking benzene is receiving increasing attention. However, the thiophene contained in coking benzene can easily lead to catalyst deactivation, severely affecting the subsequent utilization of benzene. Therefore, ultra-deep removal of thiophene from coking benzene, reducing it to below 10 ppb, has significant practical implications.

[0004] Among numerous desulfurization technologies, selective adsorption desulfurization (SAD) has become the preferred next-generation desulfurization technology due to its mild conditions and low cost. The key to SAD technology lies in the development of highly efficient desulfurization adsorbents. Y-type molecular sieves have attracted widespread attention due to their advantages such as three-dimensional pore structure, large specific surface area, abundant surface acidity, excellent size selectivity, and superior ion exchange performance. Furthermore, Y-type molecular sieve adsorption is considered one of the most competitive desulfurization methods.

[0005] Furthermore, researchers loaded active metals such as Cu and Ce onto the surface of Y-type molecular sieves using ion exchange and found that the Y-type molecular sieves after metal ion exchange exhibited good performance in removing thiophene.

[0006] Yun Zu et al. (Investigation of Cu(I)-Y zeolites with different Cu / Alratios towards the ultra-deep adsorption desulfurization: Discrimination androle of the specific adsorption active sites[J]. Chem. Eng. J.A study (2020, 380:122319.) reported a CuY molecular sieve adsorbent prepared by liquid-phase ion exchange. It exhibited good desulfurization performance for high-sulfur oils with a Cu / Al ratio of 0.28, with a breakthrough sulfur adsorption capacity of approximately 30.4 mg(S) / g. However, this method requires repeated ion exchange processes to achieve its high copper loading and the expected high ion exchange level. Furthermore, the actual loaded copper species cannot be effectively utilized, and the repeated exchange processes are not only time-consuming but also generate a large amount of waste liquid.

[0007] Therefore, adsorbents with stable and uniform sites are essential for studying structure-activity relationships. Adsorption of isolated metal atoms is a crucial sustainable chemical conversion technique due to its high atomic utilization and uniform metal sites. However, the ultra-micropore size of zeolite pores often limits its activity to diffusion, and the active sites deeply embedded beneath the crystal surface are difficult for molecules to access.

[0008] Hollow zeolite single crystals are a novel zeolite morphology, composed of bulk zeolites with very large internal cavities. Encapsulating metal nanoparticles within hollow zeolite single crystals offers an alternative design. Compared to bulk crystals where metal nanoparticles are encapsulated throughout the entire crystal volume, all metal nanoparticles in hollow nanostructures are located near the surface. Due to reactant enrichment effects, hollow nanostructures tend to adsorb more reactant molecules, concentrating them within the hollow structure. Monte Carlo theory studies show that small molecules tend to concentrate within hollow structures; furthermore, density functional theory demonstrates that concave surfaces are more suitable for adsorption than convex surfaces. Therefore, constructing isolated single-metal active sites within hollow zeolite single crystals is crucial.

[0009] Hollow M@zeolite, composed of well-isolated single metals encapsulated within hollow zeolite single crystals, not only offers advantages in atomic utilization and the resulting superior properties but also exhibits excellent cycling stability. Despite these advantages, a significant challenge remains in finding a simple method to confine the isolated metal sites within the hollow zeolite single crystals. Therefore, seeking a green, efficient, one-step synthesis method for atomically dispersed Cu@Y molecular sieves is of practical significance for the ultra-deep removal of thiophene sulfides from coking benzene.

[0010] CN 110759354A discloses a green preparation method for CuY molecular sieves used for adsorption and desulfurization. Solid waste lithium slag is mixed with an alkali flux at a mass ratio of 1.5:1 and calcined in a muffle furnace at 600℃ for 6 hours to obtain alkali-fused lithium slag as the basic raw material. Silica sol is added to the raw material to adjust the silicon-aluminum molar ratio in the raw material solution. A copper-ammonium complex prepared by copper salt and ammonia water is added to the raw material solution, followed by hydrothermal crystallization at 180℃ for 8 hours, resulting in the in-situ one-step hydrothermal synthesis of CuY molecular sieves. The static equilibrium sulfur adsorption capacity of this molecular sieve can reach 24.07 mg / g. However, the pretreatment steps for the lithium slag used as the adsorbent are relatively complex, and the lithium slag contains a large number of metal elements, which affects the crystallization of the Y molecular sieve, resulting in a relatively low static sulfur adsorption capacity. Summary of the Invention

[0011] The purpose of this invention is to provide a simple, green, and efficient one-step synthesis process for atomically dispersed hollow Cu@Y molecular sieve adsorbents and their preparation method. This adsorbent is applied to ultra-deep adsorption desulfurization in coking benzene and exhibits high adsorption and removal capacity for thiophene sulfur.

[0012] Specifically, the hollow Cu@Y molecular sieve adsorbent of the present invention is prepared according to the following method:

[0013] 1) Add aluminum source and alkali source to the aqueous solution of copper amine complex under stirring. After dissolution, slowly add silicon source to form the original sol.

[0014] 2) Add seed crystals to the original sol and stir to form the original gel;

[0015] 3) The original gel was subjected to a hydrothermal crystallization reaction at 100-250℃;

[0016] 4) Collect the hydrothermal crystallization reaction products and reflux them in ammonium nitrate solution at 60-100℃;

[0017] 5) The hollow Cu@Y molecular sieve adsorbent is obtained by calcining and refluxing the reaction product at 300-800℃.

[0018] In the hollow Cu@Y molecular sieve adsorbent prepared in this invention, the loading of Cu is 3-6% by elemental calculation, and it exists in the form of divalent copper ions. The Cu species interacts with the oxygen in the six-membered ring shared by the Y molecular sieve supercage and sodium gabion.

[0019] Furthermore, in the hollow Cu@Y molecular sieve adsorbent prepared by the present invention, the silicon-to-aluminum atomic ratio of the Y molecular sieve is preferably 2.0-3.0.

[0020] This invention does not impose any special requirements on the silicon source used in the preparation of hollow Cu@Y molecular sieve adsorbents; any conventional silicon source used to prepare various molecular sieves can be used. Furthermore, this invention preferably uses any one of silica sol, tetraethyl orthosilicate, or silica powder as the silicon source.

[0021] This invention does not impose any special requirements on the aluminum source used in the preparation of hollow Cu@Y molecular sieve adsorbents; any conventional aluminum source used in the preparation of various molecular sieves can be used. Furthermore, this invention preferably uses any one of sodium aluminate, aluminum sol, boehmite, or aluminum isopropoxide as the aluminum source.

[0022] Furthermore, the alkali source can be either sodium hydroxide or potassium hydroxide.

[0023] In this invention, the seed crystals used to add to the original sol are Y-type molecular sieves, including any one of purchased or self-made NaY molecular sieves, NH4Y molecular sieves, and USY molecular sieves.

[0024] Furthermore, the preferred hydrothermal crystallization reaction temperature of the present invention is 100-120℃.

[0025] Furthermore, the hydrothermal crystallization reaction time is 1-4 days.

[0026] Preferably, the hydrothermal crystallization reaction described in this invention can be carried out in a dynamic crystallization mode in a homogeneous reactor.

[0027] Furthermore, the product obtained by the hydrothermal crystallization reaction of the present invention is washed and dried at 80-120°C, and then placed in an ammonium nitrate solution for reflux reaction, with the preferred reflux reaction time being 4-12 hours.

[0028] Similarly, the reflux reaction product is washed, dried, and then air-calcined to prepare the hollow Cu@Y molecular sieve adsorbent, with a preferred calcination time of 6 hours.

[0029] The copper amine complex aqueous solution is obtained by adding an organic amine ligand dropwise to a copper salt solution.

[0030] Furthermore, the organic amine ligand includes, but is not limited to, any one of tetraethylenepentamine (TEPA), (3-mercaptopropyl)trimethoxysilane (MPTS), and 3-[2-(2-aminoethylamino)ethylamino]propyltrimethoxysilane (TAPTS).

[0031] Furthermore, the copper salt solution is obtained by dissolving any one of copper nitrate hexahydrate, copper chloride hexahydrate, or copper acetate hexahydrate in water as the copper source.

[0032] The hollow Cu@Y molecular sieve adsorbent prepared by the above method of the present invention encapsulates atomically dispersed Cu of different contents in a Y-type molecular sieve. The Cu species forms a strong interaction with the framework oxygen in the six-membered ring shared by the supercage and sodalite cage, resulting in a hollow Cu@Y molecular sieve adsorbent with a unique morphology.

[0033] The hollow Cu@Y molecular sieve adsorbent has an adsorption and enrichment effect. Utilizing its three-coordinate Cu(II) species with a unified coordination environment, it adsorbs thiophene through π complexation, making it a highly efficient desulfurization species. When used as a desulfurization adsorbent, it can improve the cycle stability of the adsorbent.

[0034] In particular, the hollow Cu@Y molecular sieve adsorbent prepared by the present invention is suitable for ultra-deep adsorption and removal of thiophene sulfur in coking benzene.

[0035] The hollow Cu@Y molecular sieve adsorbent prepared in this invention possesses a unique hollow structure that allows for adsorption and enrichment. Experiments have shown that the enrichment effect of reactants typically becomes more significant with increasing curvature; the greater the curvature, the more pronounced the stress change, and the stronger the electron density transfer. This transformation inevitably exacerbates the electron deficiency of the metal, leading to improved adsorption performance. The hollow Cu@Y molecular sieve adsorbent of this invention achieves a synergistic relationship between the reactant enrichment effect and the electron-metal-carrier interaction effect. When applied to the ultra-deep adsorption and removal of thiophene sulfur, it exhibits a large static sulfur adsorption capacity and a high desulfurization rate, superior to existing ordinary molecular sieve adsorbents, and has broad application prospects.

[0036] This invention employs a ligand-protected in-situ synthesis strategy to prepare hollow Cu@Y molecular sieve adsorbents. Isolated Cu ions with atomic distribution are encapsulated in hollow FAU zeolite. The Cu species therein form a strong interaction with the framework oxygen in the six-membered ring shared by the supercage and sodium gabion. Compared with ion exchange and impregnation methods, the in-situ synthesis method is simpler to prepare, eliminates post-processing steps, and saves energy. Attached Figure Description

[0037] Figure 1 These are XRD patterns of the hollow Cu@Y molecular sieve adsorbents prepared in each embodiment.

[0038] Figure 2 This is a transmission electron microscope (TEM) image of the hollow Cu@Y molecular sieve adsorbent in Example 2.

[0039] Figure 3 This is a spherical aberration electron microscope image of the hollow Cu@Y molecular sieve adsorbent in Example 2.

[0040] Figure 4 This is a graph showing the adsorption and desulfurization efficiency of the hollow Cu@Y molecular sieve adsorbent in each embodiment. Implementation

[0041] The specific embodiments of the present invention will be further described in detail below with reference to the accompanying drawings and examples. The following examples are only used to more clearly illustrate the technical solutions of the present invention, so that those skilled in the art can better understand and utilize the present invention, and are not intended to limit the scope of protection of the present invention.

[0042] Unless otherwise specified, the production processes, experimental methods, or testing methods involved in the embodiments and comparative examples of this invention are all conventional methods in the prior art, and their names and / or abbreviations are all conventional names in the art, which are very clear and distinct in the relevant application fields. Those skilled in the art can understand the conventional process steps based on the names and apply the corresponding equipment, and implement them according to conventional conditions or the conditions recommended by the manufacturer.

[0043] The various instruments, equipment, raw materials or reagents used in the embodiments of this invention are not subject to any special restrictions on their source. They are all conventional products that can be purchased through regular commercial channels and can be prepared according to conventional methods known to those skilled in the art.

[0044] The hollow Cu@Y molecular sieve adsorbent of the present invention was prepared according to the following method in the following embodiments:

[0045] Using Cu(NO3)2 with different contents as copper source, it was added to water and stirred until dissolved. The organic amine complexing agent TAPTS was added dropwise to the solution and stirred thoroughly to obtain Cu-TAPTS solution as template agent.

[0046] Add NaAlO2 and NaOH to the template agent solution, stir thoroughly until completely dissolved, then slowly add silica sol (SiO2) and stir thoroughly to form the original sol; continue to add an appropriate amount of seed crystals to the original sol and stir to form the original gel.

[0047] The original gel was transferred to a hydrothermal synthesis vessel and placed in a homogeneous reactor at 100-120℃. After hydrothermal crystallization for 1-4 days, the gel was removed, filtered, washed, and dried to obtain the hydrothermal crystallization product.

[0048] The hydrothermal crystallization product was placed in an ammonium nitrate solution and stirred under reflux at 60-100°C for 4-12 hours to remove excess copper species through sufficient ion exchange. The product was then filtered, washed, dried, and placed in a tube furnace for high-temperature calcination in air to prepare the hollow Cu@Y molecular sieve adsorbent.

[0049] The desulfurization performance of the prepared hollow Cu@Y molecular sieve adsorbent was evaluated using static adsorption experiments in an organic solvent containing thiophene. Example

[0050] Example 1

[0051] Weigh 1.53g Cu(NO3)2 and add it to 25mL of deionized water. Stir for 30min, then add 3mL of TAPTS dropwise to the solution and stir thoroughly to obtain Cu-TAPTS template agent solution.

[0052] Add 1.05g NaAlO2 and 2.52g NaOH to the template agent solution and stir for 30 minutes to dissolve completely.

[0053] 15.52g of silica sol (50wt% SiO2) was slowly added to the above solution and stirred at room temperature for 4h to form the original sol.

[0054] Add 0.5g of NaY seed crystals to the original sol and continue stirring at room temperature for 2 hours to form the original gel.

[0055] The original gel was then transferred to a hydrothermal synthesis vessel, placed in a homogeneous reactor, heated to 120°C for hydrothermal crystallization reaction for 4 days, removed, filtered, washed, and dried in an oven at 120°C.

[0056] Weigh 1g of the dried product and place it in 50ml of 1mol / L ammonium nitrate solution. Reflux and stir at 60℃ for 12h. After filtration, washing, and drying, collect the powder product and place it in a tube furnace. Calcine at 550℃ in air for 6h to obtain the hollow molecular sieve adsorbent Cu@Y-0.56.

[0057] Example 2

[0058] Weigh 1.03g of Cu(NO3)2 and follow the same procedure as in Example 1 to prepare the hollow molecular sieve adsorbent Cu@Y-0.46.

[0059] Example 3

[0060] Weigh 0.79g of Cu(NO3)2 and follow the same procedure as in Example 1 to prepare the hollow molecular sieve adsorbent Cu@Y-0.36.

[0061] Example 4

[0062] Weigh 0.67g of Cu(NO3)2 and follow the same procedure as in Example 1 to prepare the hollow molecular sieve adsorbent Cu@Y-0.26.

[0063] Example 5

[0064] Weigh 0.48g of Cu(NO3)2 and follow the same procedure as in Example 1 to prepare the hollow molecular sieve adsorbent Cu@Y-0.16.

[0065] Example 6

[0066] Weigh 0.31g of Cu(NO3)2 and follow the same procedure as in Example 1 to prepare hollow molecular sieve adsorbent Cu@Y-0.06.

[0067] Figure 1 XRD patterns of hollow Cu@Y molecular sieve adsorbents with different copper contents prepared in Examples 1-6 above are given.

[0068] Figure 1 In the figure, all samples showed typical FAU molecular sieve characteristic peaks and all samples exhibited intact crystal structures, indicating that the presence of Cu species did not destroy the framework structure of FAU molecular sieves. At the same time, no CuO characteristic peaks were detected in the figure, indicating that the Cu species were highly dispersed and there were no Cu agglomerates.

[0069] The relative crystallinity of the adsorbents in each embodiment was calculated, and the specific results are listed in Table 1. It can be seen that as the copper content increases, the crystallinity first increases and then decreases. When the added copper content is 0.46, the crystallinity reaches its maximum value.

[0070]

[0071] Figure 2 Taking Example 2 as an example, a transmission electron microscopy (TEM) morphology characterization image of the hollow Cu@Y molecular sieve adsorbent is provided. In low-magnification mode, Cu@Y-0.46 exhibits a regular crystalline appearance, is spherical, and has a hollow structure. Its crystal surface is clean and intact, without amorphous products or large Cu clusters, which proves that Cu is dispersed at the atomic level within the pores of the FAU.

[0072] Figure 3 The ultrafine structure of the hollow Cu@Y molecular sieve adsorbent was further confirmed at the atomic scale using high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM). Figure 3 This indicates that isolated, dispersed copper atoms exist in the zeolite matrix, and due to the difference in atomic contrast (Si=14, O=8, Al=13, Cu=29), copper atoms are most likely to appear as dense bright spots.

[0073] Microscopic analysis revealed that single-atom dispersed Cu atoms were successfully encapsulated within hollow Y-type zeolite, maximizing Cu utilization in adsorption desulfurization. This ultra-high dispersion also stems from the stability of Cu-TAPTS during its in-situ synthesis.

[0074] Comparative Example 1

[0075] Weigh 10g of NaY molecular sieve and place it in 50ml of 0.1mol / L copper nitrate solution. Reflux and stir at 100℃ for 4h. Filter, wash, and dry at 120℃ for 12h. Collect the powdered product and place it in a tube furnace. Calcine at 550℃ in air for 4h to obtain the molecular sieve adsorbent Cu-Y.

[0076] The copper loading of this molecular sieve adsorbent is comparable to that of the hollow molecular sieve adsorbent Cu@Y-0.46 prepared in Example 2.

[0077] Application Example 1

[0078] The desulfurization performance of the prepared hollow Cu@Y molecular sieve adsorbent was evaluated by static adsorption experiments in a cyclohexane / benzene solution containing thiophene, and compared with that of the conventional molecular sieve adsorbent Cu-Y in Comparative Example 1.

[0079] A solution was prepared using thiophene-cyclohexane with an initial sulfur concentration of 500 ppm. The hollow Cu@Y molecular sieve adsorbents prepared in each example and the comparative molecular sieve adsorbents were added to the above solution according to a liquid-to-adsorbent ratio of 100 mL / g. The ampoules were sealed and left at room temperature for 24 hours, which was considered to be the time to reach adsorption equilibrium.

[0080] A thiophene-benzene solution was prepared with an initial sulfur concentration of 500 ppm. Hollow Cu@Y molecular sieve adsorbents prepared in each example and comparative molecular sieve adsorbents were added to the above solution at a liquid-to-adsorbent ratio of 30 mL / g. The ampoules were sealed and left at room temperature for 24 h, which was considered to have reached adsorption equilibrium.

[0081] The residual thiophene content in cyclohexane / benzene solution was determined by gas chromatography. The desulfurization efficiency of the hollow Cu@Y molecular sieve adsorbent was calculated based on the change in thiophene concentration in the cyclohexane / benzene solution before and after adsorption. Specific results are shown below. Figure 4 .

[0082] Figure 4 In the table, (a) represents the desulfurization efficiency in a thiophene-cyclohexane solution with a liquid-to-solvent ratio of 100 mL / g, and (b) represents the desulfurization efficiency in a thiophene-benzene solution with a liquid-to-solvent ratio of 30 mL / g.

[0083] As can be seen from the figure, with the increase of Cu / Al ratio, the desulfurization efficiency of the in-situ synthesized hollow Cu@Y molecular sieve adsorbent in solvents cyclohexane and benzene shows a trend of first increasing and then decreasing. The hollow molecular sieve adsorbent Cu@Y-0.46 has the highest desulfurization efficiency, reaching 74.3% and 58.2%, respectively.

[0084] Meanwhile, the desulfurization efficiency of the hollow molecular sieve adsorbent Cu@Y-0.46 is significantly higher than that of the molecular sieve adsorbent Cu-Y with the same copper loading prepared by ion exchange, which has desulfurization efficiencies of only 57.9% and 25.8% in cyclohexane and benzene, respectively. This is because the location of Cu sites in Cu-Y can dynamically change, preventing thiophene from reaching its active sites. Therefore, this also highlights the importance of introducing Cu active sites through direct hydrothermal synthesis in this invention.

[0085] The overall desulfurization efficiency of different molecular sieve adsorbents in thiophene-benzene solution decreased compared to that in thiophene-cyclohexane solution, which is due to the strong competitive adsorption between benzene and thiophene. Both benzene and thiophene are adsorbed onto copper via π-complexation. When benzene is present in the solvent, the removal efficiency of thiophene decreases significantly, which is consistent with literature reports.

[0086] However, the desulfurization efficiency of the hollow molecular sieve adsorbent Cu@Y-0.46 in the thiophene-benzene solution is still significantly higher than that of Cu-Y, and the increase is more significant than that in the thiophene-cyclohexane solution. The reasons for this phenomenon are twofold: firstly, the hollow molecular sieve adsorbent Cu@Y prepared by the in-situ synthesis method has the optimal position for copper active species, which is beneficial for thiophene adsorption; secondly, the hollow structure of the hollow molecular sieve adsorbent Cu@Y is superior to that of Cu-Y, and based on the enrichment effect of adsorption, thiophene migrates into the interior of the adsorbent, achieving the enrichment of sulfides within.

[0087] The above embodiments of the present invention do not describe all details exhaustively, nor do they limit the present invention to the embodiments described above. Various changes, modifications, substitutions, and variations made by those skilled in the art to these embodiments without departing from the principles and spirit of the present invention should be included within the scope of protection of the present invention.

Claims

1. The application of a hollow Cu@Y molecular sieve adsorbent as an adsorbent for ultra-deep adsorption and removal of thiophene sulfur from coking benzene, characterized in that... The preparation method of the hollow Cu@Y molecular sieve adsorbent includes the following steps: 1) Add aluminum source and alkali source to the aqueous solution of copper amine complex under stirring. After dissolution, slowly add silicon source to form the original sol. 2) Add seed crystals to the original sol and stir to form the original gel; 3) The original gel was subjected to a hydrothermal crystallization reaction at 100-250℃; 4) Collect the hydrothermal crystallization reaction products and reflux them in ammonium nitrate solution at 60-100℃; 5) The hollow Cu@Y molecular sieve adsorbent was obtained by calcining and refluxing the reaction product at 300-800℃; The seed crystal is any one of NaY molecular sieve, NH4Y molecular sieve, and USY molecular sieve.

2. The application according to claim 1, characterized in that: The silicon source is any one of silica sol, tetraethyl orthosilicate, and silicon oxide powder; the aluminum source is any one of sodium aluminate, aluminum sol, boehmite, and aluminum isopropoxide; and the alkali source is sodium hydroxide or potassium hydroxide.

3. The application according to claim 1, characterized in that: The hydrothermal crystallization reaction temperature is 100-120℃.

4. The application according to claim 1, characterized in that: The hydrothermal crystallization reaction takes 1-4 days.

5. The application according to claim 1, characterized in that: The reflux reaction time is 4-12 hours.

6. The application according to claim 1, characterized in that: The calcination time of the reflux reaction product is 6 hours.

7. The application according to claim 1, characterized in that: The copper amine complex aqueous solution is obtained by adding an organic amine ligand dropwise to a copper salt solution, wherein the organic amine ligand is either tetraethylenepentamine or 3-[2-(2-aminoethylamino)ethylamino]propyltrimethoxysilane.

8. The application according to claim 1, characterized in that: The Cu loading in the molecular sieve adsorbent is 3-6% (elementally), and the silicon-to-aluminum atomic ratio of the Y molecular sieve is 2.0-3.0.

Citation Information

Patent Citations

  • Synthesizing Cu-Y molecular sieve with copper-amine complex as a template agent

    CN105984883A

  • Green preparation method of CuY molecular sieve for adsorption desulfurization

    CN110759354A